What Makes Genesis Different? - Joseph R. Miller (Religions, 2022)
In contrast to those who read Genesis 1 through 11 as myth, the story of Genesis is historical narrative with a theological purpose (theo-history). The Hebrew theo-history of creation was undergirded by a worldview that did not converge with her neighbors but significantly diverged from the surrounding nations. While the literary style of Genesis has elements common to other ancient mythologies, the content itself is quite distinct. Unlike other ancient cosmologies, the Hebrew worldview perceived the people, places, and events of Genesis as historical and not merely religious symbols. The divergence of the Hebrew worldview from all ancient Near East (ANE) cultures is illustrated in three observations: (1) Genesis is monotheism not polytheism/panentheism, (2) Genesis is special revelation not cultic theology, and (3) Genesis is theo-history not myth or mytho-history. These three distinctives of Hebrew cosmology reflect a unique worldview shaped by divine revelation, and because Genesis was written in the genre of theo-history, Hebrew cosmology offers us a dependable foundation for knowing something true about our material origins, shaping ethical priorities, safeguarding the sacredness of human life, directing moral decision making, recognizing the significance of historical progress, and guiding scientific inquiry into the book of nature.